Bosnia and Herzegovina : Fourth and Fifth Reviews Under the Stand-By Arrangement and Requests for Extension and Rephasing of the Arrangement. (IMF Staff Country Reports; Country Report ;, 2001)
The study focuses on corrective fiscal policies for 2000, the budgets for 2001, and the agenda for structural reform. An important issue discussed in revising the 2000 budgets was the expenditure policy required to contain spending commitments within available resources. The authorities have made some progress in the area of fiscal transparency. Despite high unemployment, major strides have been made in labor market reform, an area that has been difficult to tackle now. Progress in privatizing state-owned banks has been patchy.